DEVELOPMENT OF MAGNETORESISTIVE SENSORS FOR NANOWIRE DETECTION TARGETED AT BIOLOGICAL APPLICATIONS - Carroll, Nigel (Trinity College (Dublin, Ireland). School of Physics, 2018)
This research project has been focused on developing technologies for the detection of single segment and multi-segment magnetic nanowires using yoke shaped GMR sensors and TMR MgO-barrier magnetic tunnel junction sensors integrated into a microfluidic channel. The leading questions has been firstly can one detect the stray field of the single-segment magnetic nanowire as it passes over the sensor and secondly can one detect the magnetic segments within a multi-segment nanowire and distinguish different signal response signatures between a single segment nanowire and multisegmented nanowire. Over the past 20 years there has been a focus in utilizing advances in magnetoresistive sensors, nanowires and microfluidics leading to simpler and less expensive instrumentation. These technologies have been integrated into labon- chip biomedical platforms for applications such as magnetocardiography (MCG), magnetic cytometry (Pannetier-Lecoeur et al 2011 and Freitas et al 2012) [1, 2]. To capture and analyse the signals, a dedicated detection system is implemented. The detection system comprises of an interface for sensors and a microfluidic chip, lownoise pre and post-amplifiers, a data acquisition card, a microscope and camera. Signal detection experiments are carried out with two GMR sensors configured as a lateral gradiometer, which enabled us to detect single segment nanowires as they pass over the sensor. Detection of single metal nanowires has been demonstrated at arbitrary stand-off distance within the microfluidic channel. Two magnetic-segment “bar” code events have also been detected using the gradiometer with focused flow.
Keywords: Detection of magnetic nanowires using magnetoresistive sensors for biological applications